Biophilic Quality Matrix: A tool to evaluate the biophilic quality of a building during early design stage - Niranjika Wijesooriya; Arianna Brambilla; Lina Markauskaite (Cleaner Production Letters)
Biophilic design has gained popularity in recent times that brings multiple benefits to the built environment including the ability to strengthen the weak human-nature connectedness in sustainable building designs. Premised on the notion of biophilia, biophilic design facilitates a sensory experience that could potentially influence psychology, cognition and behaviours. Measuring the biophilic impact and the quality of the design with its sensory experience is a challenge during the early design stages. Therefore, all existing tools developed to measure the biophilic quality, focused on completed projects in the industry. In academic settings design outcome is judged during the early design stage. Hence, the existing tools could not fully support biophilic quality evaluation. To fill this gap this study proposes a Biophilic Quality Matrix, to evaluate the biophilic quality that was developed adopting three techniques of 1) literature synthesis, 2) framework synthesis, and 3) expert knowledge that included a thorough analysing of the current tools. This novel matrix type tool comprises of 10 criteria and 10 intervention scales to capture the sensory experiences that could be adapted in both conventional and sustainable studios. It was developed allowing postgraduate students to use as a self-assessment tool to scaffold learning by facilitating for evaluative judgement. Two sample evaluations are given with a validation by tutors using an interrater rating method with 92% agreement for case 1 and 93% for case 2. The statistical analysis revealed that the Cohen's kappa was .804 for Case 1 and .823 for Case 2, both indicating a strong agreement level by the tutors. Therefore, this new tool can be used in design studios to evaluate the biophilic quality. Further, this matrix contains criteria that is commonly applicable biophilic design allowing to be used in industry for real projects both during design stage and after completion with systematic validation.